HUBUNGAN PENGETAHUAN GIZI IBU BALITA DENGAN PENGELOLAAN MAKANAN SEHAT BALITA DI POSYANDU MAWAR DESA KEPUNDUNG KECAMATAN REBAN KABUPATEN BATANG JAWA TENGAH - Siti Istiharoh (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2017)
This research is intended to understanding (1) the nutrient skill level of mothers baby, (2) the management of the healty food for babies , & (3) correlation between the nutrient skill of mothers baby with the management of the healty food for babies in Mawar posyandu in the Kepundung village subdistrict of Reban the regency of Batang Central Java. This research belongs to a kind of the correlation research, ex post facto. The writer used the data accumulation method by questionnaire & dokumentation. The writer also used two techniques to analyze this data, they are descriptive analysis technique & hypotheses experiment to try the correlation Product Moment that previoused with the regulation experiment analysis, they are normality & linearity. The result of this research dedicated that their nutrient skill in the sufficient category in 53 frequency with 63,10% frequency, & the management of the healty food for babies also in the sufficient category in 59 frequency with the relative frequency is 70,24%. Based on the result hypotheses experiment is correlationed that the Product Moment is found the correlation coefficient mark of (R²) is amount of 0,661 that is consultacied in r table mark, the mark of n is about 84 which is significant level of 5% is 0,213. So, (R²) mark that found is above of r table mark is 0,661 > 0,213. It means that there was correlation between the nutrient skill of mothers with the management of healty food for babies. Key words: nutrient skill of mothers baby, management of healty food for babies